A Review Article on Staphylococcus Aureus (International Journal of Scientific Research and Management (IJSRM), 2025)
Staphylococcus is a genus of gram-positive bacteria. More than 30 species of gram-positive bacteria are present. Under a microscope, their shape is normally spherical(cocci) clusters that resemble grapes. As facultative anaerobes, staphylococcus species may grow in both aerobic and anaerobic conditions. Greek terms “staphylo” which means grapes and “coccus” which means spherical bacterium were combined to name the genus in 1880 by Scottish surgeon Alexander Ogston. It is a frequently occurring bacteria in humans and causes various illnesses, such as sepsis, pneumonia, and skin infections. With this bacterium, it can infect patients who have low immunity power such as in cases when the patient is in critical condition and those who have medical implants equipped in their body, they can also create toxins that lead to food poisoning. It creates post-surgery infection.